2011
DOI: 10.1007/s00415-011-6146-2
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled clinical trial of growth hormone in amyotrophic lateral sclerosis: clinical, neuroimaging, and hormonal results

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurological disease with motor neuron degeneration. Riluzole is the only available treatment. Two-thirds of ALS patients present with growth hormone (GH) deficiency. The aim of this study is to determine if add-on of GH to riluzole, with an individually regulated dose based on Insulin-like growth factor 1 (IGF-I) production, was able to reduce neuronal loss in the motor cortex, reduce mortality, and improve motor function of ALS patients. Patients with definite/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…GH was not found to be dangerous for motor neuron survival; rather, it showed a trophic effect on the nervous system. Moreover, GH deficiency in ALS patients has been reported in the literature (Saccà et al, 2012;Pellecchia et al, 2010). A deficiency in GH secretion similar to that seen in human ALS has been reported in hSOD1 (G39A) transgenic mice; moreover, a reduction in the expres-sion of the IGF-1 receptor α-subunit in skeletal muscle and lumbar spinal cords suggested impaired signaling within these tissues (Steyn et al, 2012).…”
Section: Exposure To Pesticides and Dietary Supplements/illegal Substmentioning
confidence: 97%
See 1 more Smart Citation
“…GH was not found to be dangerous for motor neuron survival; rather, it showed a trophic effect on the nervous system. Moreover, GH deficiency in ALS patients has been reported in the literature (Saccà et al, 2012;Pellecchia et al, 2010). A deficiency in GH secretion similar to that seen in human ALS has been reported in hSOD1 (G39A) transgenic mice; moreover, a reduction in the expres-sion of the IGF-1 receptor α-subunit in skeletal muscle and lumbar spinal cords suggested impaired signaling within these tissues (Steyn et al, 2012).…”
Section: Exposure To Pesticides and Dietary Supplements/illegal Substmentioning
confidence: 97%
“…A deficiency in GH secretion similar to that seen in human ALS has been reported in hSOD1 (G39A) transgenic mice; moreover, a reduction in the expres-sion of the IGF-1 receptor α-subunit in skeletal muscle and lumbar spinal cords suggested impaired signaling within these tissues (Steyn et al, 2012). However, a recent clinical trial failed to detect clinical and survival improvement in ALS patients administered GH (Saccà et al, 2012). Branched-chain amino acids (leucine, isolucine and valine) are widely used among athletes to stimulate muscle protein synthesis, improve physical resistance and reduce delayed onset muscular soreness.…”
Section: Exposure To Pesticides and Dietary Supplements/illegal Substmentioning
confidence: 98%
“…There have been several treatment trials using free IGF-1 therapy in amyotrophic lateral sclerosis (ALS) [68][69][70] and one trial of free IGF-1 complexed with IGF-1 binding protein-3 in myotonic dystrophy [71]. ALS trials failed to show a clear beneficial result but demonstrated safety of IGF-1 in these patients.…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
“…The trial in myotonic dystrophy showed encouraging results in seven of the nine patients treated. Two patients discontinued treatment because of cardiovascular complications [68][69][70][71][72]. More recently, treatment trials in children with primary growth hormone deficiency, elderly women following hip replacement surgery and patients with complications of HIV infection, have trialed IGF-1 complexed with IGF-1 binding protein-3, and each group of patients have tolerated this preparation without significant side effects [74][75][76].…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
“…GH has evaluated in a phase II trial (NCT00635960) with no effects on disease progression (Sacca et al, 2011).…”
Section: Growth Hormone (Gh Somatropin)mentioning
confidence: 99%